Pembagian Warisan bagi Anak Perempuan Menurut Hukum Adat Masyarakat Mandailing dan Perdata Islam - Jekson Saragih; Ruth Yesika Siahaan; Esra Natasya Sitepu; Laras sati Sintania; Putri Widia Ningsih; Sri Hadiningrum; Parlaungan Gabriel Siahaan (Journal on Education, 2024)
The Mini Research Assignment for Group 4 from Class B PPKn 2022 is entitled: "Division of inheritance for girls according to the customary laws of the Mandailing community and Islamic civil law (case study of the Tanjung Mompang village community)". This Mini Research examines the position of daughters of the Mandailing Indigenous community in the distribution of inheritance according to the customary law that applies in the Mandailing community as well as according to the distribution of Islamic civil inheritance. The aim of this research is to find out the position of daughters of the Mandailing Indigenous community in the distribution of inheritance according to the customary law that applies in the Mandailing community. This Mini Research uses Qualitative Research Methods with qualitative descriptive research presented descriptively. Data collection techniques Through literature studies by collecting some information related to the research field such as books, journals, scientific works and many other references for collecting relevant data.